Association between Exclusive breastfeeding and Picky Eater in Children Aged 1-3 Years Old at Puskesmas Kratonan Surakarta - Arifah, Umi; Lestari, Endang Dewi; Ayusari, Amelya Augusthina (Nexus Kedokteran Komunitas, 2016)
Background: Picky eaters are eating problems found in children where the child refuses certain foods or picky eating. One of the determining factors of picky eating behavior is breastfeeding. Breastfeeding provides more varied taste experience in children so that children tend not to picky and easily accept new foods. This study aimed to determine the association between exclusive breastfeeding and picky eater in children aged 1-3 years old at Puskesmas Kratonan Surakarta. Methods: This research was an analytic observational study with the cross sectional approach. Subjects were children aged 1-3 years old in Puskesmas Kratonan with total sample of 96 children. The independent variable is the exclusive breastfeeding and the dependent variable is a picky eater. Variables measured using a questionnaire that was pre-tested for its validity and reability. Data were analyzed use chi square test, on SPSS 19.0. Results: There were 43 children (44,8%) experienced a picky eater and 59 children (61,5%) exclusively breastfed. Statistical analysis of research with Chi Square test obtained values X2 = 0.058 and significance = 0.975. Conclusions: There was no association between exclusive breastfeeding and picky eater in children aged 1-3 years old at Puskesmas Kratonan Surakarta. Keywords: Picky eater, exclusive breastfeeding, Children aged 1-3 years.